The Influence of Radiological “Disappearing Lesions” on the Efficacy and Prognosis of Patients with Colorectal Liver Metastases Undergoing Conversion Therapy - Zhi-yang Song; Dong Yang; Yang Liu; Yong Cheng (Gastroenterology Research and Practice)
Purpose. The purpose of the current study was to analyze the influence of radiological “disappearing liver metastasis” (DLM) on the efficacy and prognosis of patients with colorectal liver metastases (CRLM) undergoing conversion therapy. Methods. Patients with CRLM by the multidisciplinary team (MDT) of the First Affiliated Hospital of Chongqing Medical University were retrospectively enrolled from January 2014 to January 2021. The relationship between the occurrence and recurrence of DLM and different clinical factors was analyzed. Results. Thirty-five of the 113 patients (31.0%) with initially unresectable CRLM developed DLM, and of the 361 lesions, 177 disappeared (49.0%). Within 6 months, 6-12 months, and 12-24 months groups, the recurrence rate was 3.4%, 16.8%, and 34.8%, but there is no recurrence in after 24 months group. There was a statistical difference between chemotherapy alone and chemotherapy combined with the targeted therapy group on the occurrence of DLM (58.3% vs. 37.1%, P<0.001). There were significant differences between <5 mm group and >10 mm group on occurrence of DLM（76.7% vs. 30.4%, P<0.001) and between 5-10 mm group and >10 mm group also (70.0% vs. 30.4%, P<0.001). Through univariate and multivariate analyses, it was concluded that age (P=0.026, 95%CI=3.690) and treatment regimens (P=0.033, 95%CI=2.703) had a significant influence on the progression-free survival (PFS) time of DLM. Conclusion. Younger patients, who use chemotherapy alone to achieve a therapeutic effect, might have better survival benefits when the lesions do not progress within 2 years after the appearance of DLMs.